2014
DOI: 10.3945/ajcn.113.071357
|View full text |Cite
|
Sign up to set email alerts
|

Fruit, vegetable, and fiber intake in relation to cancer risk: findings from the European Prospective Investigation into Cancer and Nutrition (EPIC)

Abstract: Fruit, vegetables, and certain components of plant foods, such as fiber, have long been thought to protect against cancer. The European Prospective Investigation into Cancer and Nutrition (EPIC) is a prospective cohort that includes >500,000 participants from 10 European countries and has made a substantial contribution to knowledge in this research area. The purpose of this article is to summarize the findings published thus far from the EPIC study on the associations between fruit, vegetable, or fiber consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
170
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(191 citation statements)
references
References 31 publications
9
170
2
3
Order By: Relevance
“…However, individuals with higher intakes of vegetables and fruit which are rich in vitamin C are likely to have other healthy behaviors, such as a lower prevalence of overweight/obesity and tobacco smoking as well as lower intakes of alcohol. 43,44 Hence, we could not fully exclude the possible impact on esophageal cancer risk of these confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, individuals with higher intakes of vegetables and fruit which are rich in vitamin C are likely to have other healthy behaviors, such as a lower prevalence of overweight/obesity and tobacco smoking as well as lower intakes of alcohol. 43,44 Hence, we could not fully exclude the possible impact on esophageal cancer risk of these confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Small cell GI LSA closely resembles feline inflammatory bowel disease (IBD) in its clinical presentation,2 with both diseases having poorly defined etiologies. Various risk factors including genetic and molecular alterations,3, 4, 5 diet,3, 6, 7 and chronic inflammation8, 9, 10 have been linked to the development of both disorders. Still other studies have suggested an association between chronic mucosal inflammation and the progression of IBD to pronounced dysplasia in the GI tract 11, 12, 13, 14…”
Section: Introductionmentioning
confidence: 99%
“…Diet may also play a role in lung cancer etiology 4, 5, 6. Among dietary factors, fruits, and vegetables are of much interest due to their potential anti‐inflammatory and antioxidant properties 7.…”
Section: Introductionmentioning
confidence: 99%